Selecting Hospital\'s Key Performance Indicators, Using Analytic Hierarchy Process Technique - Raana Gholamzadeh Nikjoo; Hossein Jabbari Beyrami; Ali Jannati; Mohammad Asghari Jaafarabadi (Shahid Sadoughi University of Medical Sciences, 2013)
Introduction: hospitals performance indicators will help monitoring, evaluation and decision making and therefore must be selected and ranked accurately. The aim of present study is identifying and selecting key hospitals performance indicators. Materials and methods: This is a descriptive and mixed (quantitative-qualitative) study. literature review and expert panel has been done to identify all performance indicators. we prioritize performance indicators by Analytical Hierarchy process (AHP) technique. The data were analyzed by Excel 2007 and Expert Choice11 software's. Results: hospital performance indicators are classified to three areas as quality- effectiveness, efficiency- financing and accessibility - equity. Indicators like the rate of hospital average length of stay in hospital based on different diagnosis and the mean rate of inpatient waiting time are considered with highest priority performance indicators of public hospitals. Conclusion: Identifying hospital's key performance indicators provides an opportunity for health stakeholders to identify critical and problematic points with lower costs and time and to the best correction action.